Role of insulin like growth factor axis in the bleomycin induced lung injury in rats - Kotarkonda, Lakshmi Kanth; Kulshrestha, Ritu; Ravi, Krishnan (Experimental and molecular pathology, 2017)
Alveolar epithelial cell injury has been proposed as a causative factor for the onset and progression of pulmonary fibrosis. However, the role of type II alveolar epithelial cells (AECs) in the epithelial mesenchymal transition (EMT) is controversial. The present study performed in rats instilled with bleomycin investigated a) the expressions of the insulin growth factor (IGF-1) and insulin growth factor binding protein 5 (IGFBP-5) and transforming growth factor (TGF-β1) in the type II AECs, b) the role of type II AECs in EMT and extracellular matrix (ECM) formation and, c) the effect of pioglitazone on all the above parameters. Male Wistar rats were divided into three Groups: Group I (saline control), Group II (Bleomycin, given as a single intratracheal instillation, 7U/kg) and Group III (Bleomycin+Pioglitazone (40mg/kg/day orally, starting 7days post bleomycin instilled as in Group II). From lung tissues, the protein expressions of IGF-1, IGFBP-5, TGF-β1, surfactant protein C (SP-C, as a marker for type II AECs) and α-smooth muscle actin (α-SMA, as a marker for EMT), were determined on day 7 in Groups I and II and on days 14, 21 and 35 in all the three groups. IGFBP-5 and IGF-1 expressions were reduced significantly and TGF-β1 expression increased significantly in type II AECs in Group II from day 7 till day 35 as compared to Group I. An increase in SP-C and α-SMA expression and their co-localization were seen in the type II AECs undergoing EMT from day 7 till day 35. A concomitant remodeling and laying down of ECM was observed also. In Group III, with pioglitazone, there was a reversal with significant up-regulation in IGFBP-5 and IGF-1 expressions and down-regulation of TGF-β1 in the type II AECs along with a significant decrease in the solid area fraction, EMT and ECM in the lung tissue. IGFBP-5, IGF-1 and TGF-β1 in the type II AECs play a key role in lung injury caused by bleomycin and pioglitazone attenuates the lung injury/fibrosis by restoring IGFBP-5 and IGF-1 and decreasing TGF-β1 expressions in the type II AECs.